Assessment of the Level of Quality Control of Cement and Sandcrete Block Materials Available in Maiduguri Metropolis - Abba, M. A.; Kadai, B.; Garga, A. B.; Musa, A. M.; Hassan, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Variations in material properties, such as strength or durability, material defects and substandard materials can affect the structure’s performance. This study assesses the level of quality control of building materials (Cement, sand and blocks) available in Maiduguri Metropolis. Generally, it included the Survey and collection of data of the existing supply markets, samples collection, laboratory tests, and analyses of results were conducted. Observation made from the survey showed that the price of blocks 150mm and 225mm thick range from 450 - 500 naira and 550 - 650 naira respectively. The particle size distribution of the sand sample used in the sand combination shows that the sand fell mostly in zone 2 except one which fell in zone 3 in accordance with Federal Ministry of Works and Housing Design Manual (FMWH). The average dry density of the investigated sandcrete blocks ranged from 1777.10kg/m3 - 2098.67kg/m3. The average compressive strength of the 150 mm thick blocks ranged between 0.12 - 0.45N/mm2. The maximum value 0.45N/mm2 recorded is less than 85% of the recommended minimum strength. The findings on the hydration properties of cement are within the BS 449 standard. The results show that the quality control of the building materials in Maiduguri Metropolis is generally inadequate, with many suppliers and contractors are unaware or failing to adhere to standard specifications and regulations.